School Quality Culture as a Means of Shaping Students' Morals: Budaya Mutu Sekolah sebagai Sarana Pembentukan Akhlak Peserta Didik - Veninda Ramadhan; Hafidz (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Education plays a vital role in shaping students’ morality, supported not only by curriculum but also by the school’s cultural environment. Specific Background: Amid declining educational quality and increased moral issues such as student absenteeism and disrespectful behavior, schools need systematic approaches to character development. Knowledge Gap: Existing studies often focus on religious teachers' roles, overlooking the collective effort of all school members through a structured quality culture. Aims: This study investigates the implementation of school quality culture in shaping student morality at SMP Negeri 1 Masaran. Results: Using a qualitative case study approach, the findings reveal that moral improvement is fostered through habitual programs such as the